Hand washing system based on internet of things - Lastin, Diokta Redho; Banowosari, Lintang Yuniar (Jurnal Mandiri IT, 2025)
In December 2019, the first case of mysterious pneumonia was reported in Wuhan, Hubei Province. The source of transmission of this case is still unknown, but the first case was linked to a fish market in Wuhan. According to Packham in his research entitled Hand Hygiene for Infection Prevention Against COVID-19, there are two main approaches to hand decontamination, the first is to remove the virus, and the second is to inactivate the virus so that even if the virus is transferred it will not cause harm. Water is a vital resource for life. Water is used for activities such as drinking, bathing, cooking, and washing. Therefore, the availability of sufficient water is highly prioritized in both urban and rural areas. This research aims to create a handwashing warning system based on the Internet of Things (IoT) as a preventive measure against the spread of COVID-19 which is controlled and monitored for use through an Android device.